Genetics : analysis and principles / Robert Brooker. - Brooker, Robert J. (McGraw Hill, 2023)
'Genetics' is a one-semester, introductory genetics textbook that takes an experimental approach to understanding genetics. By weaving one or two experiments into the narrative of each chapter, students can simultaneously explore the scientific method and understand the genetic principles that have been learned from these experiments. The pedagogy of 'Genetics' has been designed to foster student learning. Instead of being a collection of facts and figures, this text is intended to be an engaging and motivating textbook in which formative assessment allows students to move ahead and learn the material in a productive way.